Volatile Anaesthetics and Postoperative Delirium in Older Surgical Patients – A Secondary Analysis of Prospective Cohort Studies - Kinjo, Sakura (Acta Anaesthesiol Scand, 2018)
BACKGROUND: Volatile Anaesthetics (VAs) may be associated with postoperative delirium (POD). However, to date, the effects of VAs on POD are not completely understood. The objective of this study was to investigate the incidence of POD in different VA groups. METHODS: A secondary analysis was conducted using a database created from prospective cohort studies in patients who underwent elective major non-cardiac surgery. Patients who received general anaesthesia with desflurane, isoflurane or sevoflurane were included in the study. POD occurring on either of the first two postoperative days was measured using the Confusion Assessment Method. RESULTS: Five hundred and thirty two patients were included in this study, with a mean age of 73.5 ± 6.0 years (range, 65–96 years). The overall incidence of POD on either postoperative day 1 or 2 was 41%. A higher incidence of POD was noted in the desflurane group compared with the isoflurane group (Odds Ratio=3.35, 95% CI=1.54–7.28). The incidence of POD between the sevoflurane and isoflurane or desflurane group were not statistically significant. CONCLUSION: Each VA may have different effects on postoperative cognition. Further studies using a prospective randomized approach will be necessary to discern whether anaesthetic type or management affects the occurrence of postoperative delirium.